Proteção social : a experiência dos adolescentes em acolhimento institucional - Portella, Elisandra Muniz Bento (2012)
This research paper aims to analyze the interfaces between the institutional accommodation and the experiences of adolescents under protective measure with the social protection. The legal marks of the Federal Constitution of 1988 have been discussed from historical roots of training and conception on social protection and subjects of rights, and the Statute of the Child and Adolescent, ECA, which has brought a new paradigm since its promulgation, revoking the conception of the doctrine of the irregular situation of the old Code of Minors, has proposed a new vision for Brazilian children and adolescents: the integral protection. Moreover, ECA has, by being signed in the Convention on the Rights of the Child from the Federal Constitution, assured family rights and duties, State and society, even as, after its promulgation, the System of Human Rights (SGD) and the National Plan for Promoting Family and Community Acquaintanceship (PNCFC) that were instituted for standardizing and orienting socio-assistance services and the integral protection of the child and adolescent.This research has also utilized empirical data coming from individual interviews realized with nine (09) adolescents under protection measure in the Foundation of Special Protection of the State of Rio Grande do Sul that have been close to institutional shutting down by virtue of civil adulthood. In addition, the investigation aims not only to analyze the social experience of adolescents accommodated in the protective institution, but also address knowledge of their social and family experiences, their rights that are ensured and violated, and their perspective in the System of Human Rights. Therefore, some conclusions may be drawn from this study, such as: the (non) visualization of the subjects through public social policies that develop focused, fragmented and disarticulated actions, child and adolescent care policy, and the vision of the adolescents of the institutional accommodation about family, which is always idealized and never reached, beyond being contradictorily represented by the institution, although expressing precariousness and also some experience of precarious inclusion. Thus, this work has searched for conferring visibility to the institutionalized youth, contributing for the discussion and reflection, providing the transformation of this reality to one that may preserve rights and ensure an effective social protection of these subjects.